Assessment of non‐vitamin K antagonist oral anticoagulants for the management of left ventricular thrombus. Issue 6 (2nd April 2021) - Li, Shunhui; Deng, Yuqing; Tong, Yifan; Xiong, Qiangzhen; Hu, Jing; Jiang, Xiaojie; He, Tao; Liu, Liyun; Chen, Hui
Abstract: Although several studies have assessed the effect of non‐vitamin K antagonist oral anticoagulants (NOACs) relative to that of vitamin K antagonists (VKAs) in patients with left ventricular thrombus, the results remain controversial. Herein, a meta‐analysis was performed to compare the effectiveness and safety of NOACs versus VKAs for the treatment of left ventricular thrombus. We systematically searched the Cochrane Library, PubMed and Embase databases until November 2020 for studies that compared the effects of NOACs versus VKAs in patients with left ventricular thrombus. The treatment effects were expressed as odds ratios (ORs) with 95% confidence intervals (CIs) and pooled by a random‐effects model. Seven retrospective studies involving 865 patients with left ventricular thrombus (266 NOAC and 599 VKA users) were included. The pooled analysis suggested no difference in the rate of thrombus resolution between the NOAC and VKA groups (OR = 0.83, 95% CI 0.61–1.13). There were also no differences in the rates of stroke or systemic embolism (OR = 0.62, 95% CI 0.20–1.97), bleeding events (OR = 0.73, 95% CI 0.37–1.45), or all‐cause death (OR = 0.92, 95% CI 0.50–1.69) between patients treated with NOACs and those treated with VKAs. In addition, the rates of thrombus resolution, stroke or systemic embolism, bleeding events, and all‐cause death between NOAC‐ and warfarin‐treated patients were also similar. Our current evidence suggested that NOAC and VKA users had similar rates of thrombus resolution and clinical outcomes among patients with left ventricular thrombus. Further large‐scale prospective studies should confirm our results.